2017
DOI: 10.1007/s00380-017-1079-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired left ventricular diastolic function is related to the formation of left ventricular apical thrombus in patients with acute anterior myocardial infarction

Abstract: Left ventricular (LV) apical thrombus is a clinically important complication which can cause systemic embolization in patients with anterior acute myocardial infarction (AMI). Systolic dysfunction has been a risk factor for developing LV apical thrombus in AMI patients. However, the role of diastolic dysfunction in the development of LV apical thrombus in these patients is still unknown. We performed this study to evaluate whether diastolic dysfunction can influence the development of LV apical thrombus in ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Cardiac thrombi in ischemic cardiomyopathy usually develops in patients with severely impaired left ventricular ejection fraction. 12,13 Our .1%, respectively, in one study. 4 There were also reported cases of aortic thrombi.…”
Section: Discussionmentioning
confidence: 82%
“…Cardiac thrombi in ischemic cardiomyopathy usually develops in patients with severely impaired left ventricular ejection fraction. 12,13 Our .1%, respectively, in one study. 4 There were also reported cases of aortic thrombi.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, percutaneous coronary intervention has replaced thrombolytic therapy as an effective means of decreasing the incidence of LV apical thrombi. Our previous study showed that the incidence of LV apical thrombi was 3.3% (34 of 1,045) in patients with acute anterior MI, and it was associated with impaired diastolic function 11)…”
Section: Discussionmentioning
confidence: 96%
“…LV thrombus after AMI is a clinically important complication that can cause systemic embolization. Recent reports showed the incidence of LV thrombus was about 1.5%-3% in the primary PCI era [4,5]. The risk factors associated with LV thrombus include delayed reperfusion, anterior AMI, large infarct size, aneurysmal change of LV apex, and cardiac dysfunction [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed the incidence of LV thrombus was about 1.5%-3% in the primary PCI era [4,5]. The risk factors associated with LV thrombus include delayed reperfusion, anterior AMI, large infarct size, aneurysmal change of LV apex, and cardiac dysfunction [5]. Although there are few data regarding embolic complications by LV thrombus in patients undergoing primary PCI, embolic complications in the thrombolytic era occurred in 2%À3% of patients with LV thrombus [6].…”
Section: Discussionmentioning
confidence: 99%